2021
DOI: 10.1177/03008916211053048
|View full text |Cite|
|
Sign up to set email alerts
|

Lung metastasectomy for osteosarcoma in children, adolescents, and young adults: proof of permanent cure

Abstract: Introduction Surgical resection of pulmonary metastases has been associated with increased survival at 5 years for osteosarcoma, but limited information is available on long-term outcome, role of repeated metastasectomies, and surgical sequelae in a pediatric population. We analyzed a consecutive series of children, adolescents, and young adults (AYA) treated by repeated lung metastasectomies during a period >40 years to estimate the clinical benefit and potential cure rate of salvage surgery. Methods All p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The rapid progression and metastasis of OS pose significant challenges for its treatment. Approximately 20% of patients present with lung metastasis at the time of diagnosis, and the majority of recurrent OS cases involve lung metastasis ( Pastorino et al, 2023 ). Current standard treatments for OS include neoadjuvant chemotherapy, surgical resection of the primary tumor, and adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid progression and metastasis of OS pose significant challenges for its treatment. Approximately 20% of patients present with lung metastasis at the time of diagnosis, and the majority of recurrent OS cases involve lung metastasis ( Pastorino et al, 2023 ). Current standard treatments for OS include neoadjuvant chemotherapy, surgical resection of the primary tumor, and adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Ugo et al studied 463 children, adolescents, and young adults with pulmonary metastases from osteosarcoma, with a median age of 15.9 years (range 0.2-23.2 years). The multivariate analysis revealed that the disease-free interval, the number of metastases, and complete resection of the primary tumor were the most important factors predicting survival [31]. The independent risk factors for pulmonary metastasis of pediatric osteosarcoma were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…11 For decades, thoracotomy has been the primary surgical approach in order to manually identify radiographically undetectable lesions by palpating calcified microscopic OST nodules. 12 Thoracotomy with manual exploration of lungs continues to be the recommended surgical approach in metastatic OST. In contrast, since the emergence of videoassisted thoracoscopic surgery (VATS) in the early 1990s as a minimally invasive alternative approach for lung cancer surgery, VATS has been established as the gold standard for surgical resection of early-stage lung cancer, 13 and is increasingly being utilized to resect pulmonary metastases in many cancers, including OST.…”
Section: Discussionmentioning
confidence: 99%
“…Aggressive PMs have been shown to improve survival in patients with metastatic OST since the 1970s 11 . For decades, thoracotomy has been the primary surgical approach in order to manually identify radiographically undetectable lesions by palpating calcified microscopic OST nodules 12 . Thoracotomy with manual exploration of lungs continues to be the recommended surgical approach in metastatic OST.…”
Section: Discussionmentioning
confidence: 99%